FROM DISSENT TO DISCIPLINE: DEMOCRACY WITH CHINESE CHARACTERISTICS IN HONG KONG - Xie, Colin Mianqing (Malaysian Journal of International Relations, 2025)
Hong Kong’s political evolution since the 2019 protests has intensified Beijing’s recalibration of governance under the rubric of “democracy with Chinese characteristics.” Through the enactment of the National Security Law, sweeping electoral reforms, and the institutionalisation of the “patriots governing Hong Kong” principle, the city has transitioned from pluralistic contestation to a well-ordered participation model. Yet limited attention has been given to how Hong Kong is deployed as a showcase for legitimising China’s democratic paradigm. This article addresses whether Hong Kong can still be considered a “semi-democracy,” and, if not, what alternative classification is appropriate. Drawing on official white papers, policy addresses, and key legal texts, the analysis situates Hong Kong within wider debates on the operationalisation of “democracy with Chinese characteristics” and the resilience of authoritarian governance.